INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM PERGURUAN TINGGI UMUM MELALUI LEMBAGA DAKWAH KAMPUS - Lukis Alam (Postgraduate Program Magister Pendidikan Agama Islam, 2016)
Education is a right for everyone, which can enhance human dignity, therefore Islam advocate it. Accordingly, the actions and activities should be oriented towards the goals set. Thus the true education should be oriented towards the objectives to be achieved, one of which is the education of Islam in public colleges. Islamic education is one of the compulsory subjects and the basis for the development of personality of students. The most important personality of a student is when he was in the act and behaves always underlies the elements of the knowledge of faith, piety and noble character who has known the basis for all kinds of knowledge, skill or expertise. Related to this there are activities organized by the students, known as Propagation Institute Campus, as a vehicle that becomes a resource for students to implement his knowledge of Islam, the institution of propaganda campus can be a vehicle collaborator for Islamic religious education formally in the classroom, which is expected to providing awareness internalization of religious values to students simultaneously. This study uses a critical review of the campus propaganda agencies in order to internalize the values of religion, while the analysis is descriptive-narrative. Therefore, this study is literacy derived from primary documents and secondary, so it is qualitative. Thus this study can serve as a reference for academics / practitioners in order to see the extent to which Islamic religious education can provide internalization of religious values to students.